2021
DOI: 10.3389/fmars.2021.730984
|View full text |Cite
|
Sign up to set email alerts
|

Technical and Social Approaches to Study Shoreline Change of Kuakata, Bangladesh

Abstract: In recent years, shoreline determination has become an issue of increasing importance and concern, especially at the local level, as sea level continues to rise. This study identifies the rates of absolute and net erosion, accretion, and shoreline stabilization along the coast of Kuakata, a vulnerable coastal region in south-central Bangladesh. Shoreline change was detected by applying remote sensing and geographic information system (RS-GIS)-based techniques by using Landsat Thematic Mapper (TM), Landsat 8 Op… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 61 publications
0
9
0
Order By: Relevance
“…Perennially the world's most ubiquitous and expensive natural hazard, flooding increases in notoriety as populations and economic investment in coastal and other flood-prone areas continue to climb sharply (Dewan et al, 2006;Bushra et al, 2021). One way to enhance flood risk preparedness is through improved flood risk communication (Maidl and Buchecker 2015), especially that which provides actionable information such as previous, current, and future flood damage (Mostafiz et al, 2021a) and hazard risk, mitigation and adaptation approaches, and cost-benefit analysis.…”
Section: Introduction: Communication For Minimizing Flood Riskmentioning
confidence: 99%
“…Perennially the world's most ubiquitous and expensive natural hazard, flooding increases in notoriety as populations and economic investment in coastal and other flood-prone areas continue to climb sharply (Dewan et al, 2006;Bushra et al, 2021). One way to enhance flood risk preparedness is through improved flood risk communication (Maidl and Buchecker 2015), especially that which provides actionable information such as previous, current, and future flood damage (Mostafiz et al, 2021a) and hazard risk, mitigation and adaptation approaches, and cost-benefit analysis.…”
Section: Introduction: Communication For Minimizing Flood Riskmentioning
confidence: 99%
“…The perilous and expensive nature of flood hazards calls for concurrent improvements in the ability of scientists to measure their risk (Kron, 2005 ). Moreover, rapid increases in the population living in marginal areas relative to the flood hazards (Moulds et al, 2021 ), amid the consequences of land use changes such as in Bangladesh (Dewan et al, 2007 ), Belgium (Akter et al, 2018 ), India (Guhathakurta et al, 2011 ), China (Shen et al, 2021 ), the United States (Qiang et al, 2017 ), and elsewhere, a changing climate (Zhou et al, 2012 ; Kreibich et al, 2015 ), sea level rise (Nicholls et al, 1999 ; Bushra et al, 2021 ), and local factors such as subsidence (Mostafiz et al, 2021a ) and extreme weather events (Guhathakurta et al, 2011 ), underline the urgent need for accelerated improvements in flood risk assessment (Merz et al, 2014 ; Mostafiz, 2022 ). Yet proportionately little advancement has been made.…”
Section: Introductionmentioning
confidence: 99%
“…The most comprehensive recent study on ESLR is by Oppenheimer et al (2019), as part of the Intergovernmental Panel on Climate Change (IPCC), who reported a rise of 1-2 mm year −1 in most regions through the twentieth century, with current rates of 3-4 mm year −1 . Predictions of future ESLR hinge on the extent to which societal changes may mitigate or increase the warming (Bushra et al, 2021). Intergovernmental Panel on Climate Change (2021) defines several "representative concentration pathways" (RCPs) scenarios, named for the number of Watts per square meter of additional radiative forcing that is assumed to occur in that scenario.…”
Section: Sea Level Risementioning
confidence: 99%